Macaca nemestrina and Dengue Virus Infectivity: a Potential Model for Evaluating Dengue Vaccine Candidates - SUSANA WIDJAJA; IMELDA WINOTO; JONATHAN STURGIS; CHAIRIN N MAROEF; ERLIN LISTIYANINGSIH; RATNA TAN; JOKO PAMUNGKAS; PATRICK J BLAIR; DONDIN SAJUTHI; KEVIN RANDALL PORTER (Indonesian Society for microbiology, 2010)
Macaca nemestrina has been shown to respond to infectious disease agents, such as HIV, and is more sensitive compared to other species of macaques such as rhesus (M. mulatta) and cynomolgus monkeys (M. fascicularis). To evaluate M. nemestrina for the ability to support dengue (DEN) viremia and serve potentially as an improved model for testing DEN vaccines, a series of experiments were conducted using primary viral isolates from individuals with DEN virus infections. This study shows that M. nemestrina develops consistent, measurable viremia with all four DEN serotypes and produces immune responses sufficient to protect against homologous virus. Anti-dengue antibodies generated after infection are predominately IgG1. This species of monkey therefore appears to be a suitable model for testing DEN virus vaccine candidates.